2021
DOI: 10.1155/2021/7617839
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Melanocyte Apoptotic Bodies in Vitiligo and the Relocation of Vitiligo Autoantigens under Oxidative Stress

Abstract: Background. Oxidative stress has a vital role in the early stages of vitiligo. Autoantigens released from apoptotic melanocytes (MC) under oxidative stress are involved in the presentation and recognition of antigens. However, the transport of autoantigens to the cell surface and their release to the extracellular environment are still unclear. Apoptotic bodies (ABs) have always been considered as a key source of immunomodulators and autoantigens. Yet, the role of ABs in the immune mechanism of vitiligo is sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…However, after taVNS, the MDA concentration significantly decreased, and SOD and CAT activities were restored ( p < 0.05). Oxidative stress can induce apoptosis of melanocytes in the skin, resulting in reduced tyrosinase synthesis in apoptotic melanocytes [ 21 , 22 ]. We measured the level of tyrosinase in mouse skin, and the results showed a significant reduction in tyrosinase content in the skin of vitiligo mice.…”
Section: Resultsmentioning
confidence: 99%
“…However, after taVNS, the MDA concentration significantly decreased, and SOD and CAT activities were restored ( p < 0.05). Oxidative stress can induce apoptosis of melanocytes in the skin, resulting in reduced tyrosinase synthesis in apoptotic melanocytes [ 21 , 22 ]. We measured the level of tyrosinase in mouse skin, and the results showed a significant reduction in tyrosinase content in the skin of vitiligo mice.…”
Section: Resultsmentioning
confidence: 99%
“…The Human vitiligo melanocyte cell line PIG3V was a gift from Professor Chunying Li (Xijing Hospital of Air Force Medical University, Xi’an, China) and cultured (2×10 5 cells/mL) in a 6-well plate (2mL/well) supplemented with DMEM/F12, 10% FBS, basic fibroblast growth factor (10ng/mL), phorbol myristate acetate (10ng/mL), and penicillin/streptomycin (10000U/mL, 10000μg/mL) at 37°C in 5% CO 2 for 24 hours. 30 The cultured PIG3V cells were randomly divided into an HCQ group and a control group. Cells in the HCQ group were treated with 1μg/mL HCQ (Sigma-Aldrich Corp., St. Louis, MO, USA) for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, these findings suggest the involvement of the TNF-α/TNFR pathway and IFN-γ pathway in melanocyte apoptosis of vitiligo. Current studies have found that tyrosinase-related protein (TYRP-1) and cleavage nuclear membrane antigen Lamin A/C (Asp230) can translocate into the apoptotic bodies of melanocytes [ 57 ]. The formation of melanocyte apoptotic bodies in vitiligo is mediated by the cytoskeletal protein activation pathway and the JNK-related apoptosis pathway [ 57 ].…”
Section: Antioxidative Defense and Cellular Responses To Ros Accumula...mentioning
confidence: 99%
“…Current studies have found that tyrosinase-related protein (TYRP-1) and cleavage nuclear membrane antigen Lamin A/C (Asp230) can translocate into the apoptotic bodies of melanocytes [ 57 ]. The formation of melanocyte apoptotic bodies in vitiligo is mediated by the cytoskeletal protein activation pathway and the JNK-related apoptosis pathway [ 57 ]. This study links melanocyte apoptosis and cellular immunity in vitiligo pathogenesis.…”
Section: Antioxidative Defense and Cellular Responses To Ros Accumula...mentioning
confidence: 99%